Limb cellulitis in rural setting in India: a case control study - Deshpande, Swati G.; Grover, Ankur; Shahapurkar, Vinay V.; Shinde, Raju K. (International Surgery Journal, 2017)
Background: Cellulitis is the bacterial infection of dermis and the subcutaneous layer. Limb cellulitis is the most common and yet least studied form. This study aims at studying clinical profile, management and complications of limb cellulitis in inpatients at an Indian rural hospital. Methods: After taking institutional ethics committee approval, patients admitted to Jawaharlal Nehru medical college and Acharya Vinoba Bhave rural hospital, Wardha, Maharashtra, India with limb cellulitis during April 2007 to September 2009 were included. Their history, clinical examination and photographs were noted. They were treated conservatively or surgically depending on severity and followed up till complete recovery or 30 days after discharge whichever was earlier. Results: 130 patients i.e. 40 (30.77%) females and 90 (69.23%) males were included in this study with farming being commonest occupation. Commonest risk factor was bare foot working while least common was venous insufficiency. Right lower limb was frequently affected. Local swab cultures were sterile in 74 (56.92%) patients while E. coli grew predominantly in positive cultures and all blood cultures were negative. 84 (64.62%) patients were treated conservatively and only 46 (35.38%) required surgical intervention. 125 (96.15%) patients showed complete recovery while 5 (3.85%) patients succumbed to illness due to sepsis and multiorgan dysfunction syndrome. Conclusions: Limb cellulitis is a common disease to outpatient department and needs admission in patients with elevated risk factors. Most cases can be managed conservatively and seldom surgical intervention. Though majority can be cured completely, few with elevated risk succumb to the disease.